Passive Immunotherapy in Simian Immunodeficiency Virus-Infected Macaques Accelerates the Development of Neutralizing Antibodies - Haigwood, Nancy L. (American Society for Microbiology, 2004)
Passively transferred neutralizing antibodies can block lentivirus infection, but their role in postexposure prophylaxis is poorly understood. In this nonhuman-primate study, the effects of short-term antibody therapy on 5-year disease progression, virus load, and host immunity were explored. We reported previously that postinfection passive treatment with polyclonal immune globulin with high neutralizing titers against SIVsmE660 (SIVIG) significantly improved the 67-week health of SIVsmE660-infected Macaca mulatta macaques. Four of six treated macaques maintained low or undetectable levels of virus in plasma, compared with one of ten controls, while two rapid progressors controlled viremia only as long as the SIVIG was present. SIVIG treatment delayed the de novo production of envelope (Env)-specific antibodies by 8 weeks (13). We show here that differences in disease progression were also significant at 5 years postinfection, excluding rapid progressors (P = 0.05). Macaques that maintained ≤10(3) virus particles per ml of plasma and ≤30 infectious virus particles per 10(6) mononuclear cells from peripheral blood and lymph nodes had delayed disease onset. All macaques that survived beyond 18 months had measurable Gag-specific CD8(+) cytotoxic T cells, regardless of treatment. Humoral immunity in survivors beyond 20 weeks was strikingly different in the SIVIG and control groups. Despite a delay in Env-specific binding antibodies, de novo production of neutralizing antibodies was significantly accelerated in SIVIG-treated macaques. Titers of de novo neutralizing antibodies at week 12 were comparable to levels achieved in controls only by week 32 or later. Acceleration of de novo simian immunodeficiency virus immunity in the presence of passively transferred neutralizing antibodies is a novel finding with implications for postexposure prophylaxis and vaccines.